Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.pharmthera.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine signaling system in progression of lung cancers

Abstract: The neurotransmitter acetylcholine (ACh) acts as an autocrine growth factor for human lung cancer. Several lines of evidence show that lung cancer cells express all of the proteins required for the uptake of choline (choline transporter 1, choline transporter-like proteins) synthesis of ACh (choline acetyltransferase, carnitine acetyltransferase), transport of ACh (vesicular acetylcholine transport, OCTs, OCTNs) and degradation of ACh (acetylcholinesterase, butyrylcholinesterase). The released ACh binds back t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 374 publications
4
92
0
Order By: Relevance
“…The role of nAChRs has been intensely studied in the growth, angiogenesis and metastasis of lung cancer . The reason for this trend is due to GWAS studies showing genetic variations in α5‐α3‐β4 nAChR cluster (CHRNA5‐CHRNA3‐CHRNB4) associated with increased risk of death from lung cancer, COPD and tobacco‐related cancers .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of nAChRs has been intensely studied in the growth, angiogenesis and metastasis of lung cancer . The reason for this trend is due to GWAS studies showing genetic variations in α5‐α3‐β4 nAChR cluster (CHRNA5‐CHRNA3‐CHRNB4) associated with increased risk of death from lung cancer, COPD and tobacco‐related cancers .…”
Section: Discussionmentioning
confidence: 99%
“…ChIP assays confirmed that the CHRNA5 promoter The role of nAChRs has been intensely studied in the growth, angiogenesis and metastasis of lung cancer. 13,30 The reason for this trend is due to GWAS studies showing genetic variations in α5-α3-β4 nAChR cluster (CHRNA5-CHRNA3-CHRNB4) associated with increased risk of death from lung cancer, COPD and tobacco-related cancers. 14,31 Conventionally, the α7-nAChR is thought to mediate the proliferative, pro-angiogenic and pro-metastatic activity of nicotine in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acetylcholine is known to be secreted by lung cancer cells into the extracellular environment, stimulating growth of cancerous cells in lung tumors 65,66 . It acts as an autocrine growth factor for human lung cancer 67 by binding to nicotinic and muscarinic receptors on lung cancer cells, accelerating their proliferation, migration, and invasion 67 . Acetylcholine was found to have mitogenic effects in A549 and in p53-negative human lung carcinoma NSCLC H1299 cells, increasing the expression of matrix metalloproteinases and downregulating the expression of E-cadherin in A549 human NSCLC 61,67 .…”
mentioning
confidence: 99%